Tinjauan Filsafat Politik terhadap Pemikiran Madilog Tan Malaka - Bhakti, Novran Juliandri; Rintia, Rintia (DAS Institute, 2025)
Tan Malaka's thought, encapsulated in Materialism Dialectics Logic (Madilog), presents a critical philosophical approach to colonialism and the Indonesian liberation struggle. This article examines Madilog's concept within the context of political philosophy, exploring the application of dialectical materialism in interpreting Indonesia’s colonial socio-political reality. Utilizing a literature review method, this article focuses on three principal elements in Madilog materialism, dialectics, and logic as intellectual and political strategies against colonial injustice. The study concludes that Tan Malaka’s approach in Madilog is a foundational influence on Indonesia's political movement history, with potential applications in modern political studies. This foundational influence not only shaped the early resistance against colonial rule but also continues to resonate in contemporary political discourse. By revisiting Madilog, scholars and activists alike can draw valuable lessons on the importance of critical thought and collective action in the ongoing struggle for justice and equity.